Knowledge of HIV/AIDS transmission modes and attitudes toward HIV/AIDS infected people and the level of HIV/AIDS awareness among the general population in the kingdom of Saudi Arabia: A cross-sectional study - Fadi S. Qashqari; Radi T. Alsafi; Saeed M. Kabrah; Rayda'a A. AlGary; Sara A. Naeem; Malak S. Alsulami; Hatim Makhdoom (Frontiers Media S.A., 2022)
IntroductionThe human immunodeficiency virus (HIV) and acquired immunodeficiency syndrome (HIV/AIDS) are worldwide public health issues. Since Saudi Arabia is growing more accessible to the outside world, it is critical to analyze the general population's knowledge of HIV/AIDS transmission modes and attitudes toward HIV/AIDS infected people, and the level of HIV/AIDS awareness. Therefore, this study aimed to assess the knowledge of HIV/AIDS transmission modes and attitudes toward HIV/AIDS infected people, as well as the level of HIV/AIDS awareness among the general population in the Kingdom of Saudi Arabia.MethodsThe current online community-based cross-sectional descriptive study was conducted among the general population of the Kingdom of Saudi Arabia using a self-administrated electronic questionnaire between October 2017 and February 2018. A score <3 was considered a negative response. In contrast, scores of 3 and 4 were considered positive responses. The sum score of each outcome was evaluated according to Bloom's cutoff point. The scores for knowledge and attitude were transformed into mean percentage scores by dividing the sum scores obtained by the respondents by the number of items multiplied by 100. Consequently, the overall mean percentage of scores for each category of knowledge and attitude at 60% and above was considered a good level, whereas <60% was deemed a poor level.ResultsA total of 2,081 subjects residing in the Kingdom of Saudi Arabia participated in this survey. The mean score of the participant's responses to knowledge items on HIV/AIDS transmission modes was 84.2 ± 15.8%. The mean score of the participant's responses to attitude items toward HIV/AIDS infected people was 50.1 ± 49.9%. The mean score of the participant's responses to attitude items toward the level of HIV/AIDS awareness in Saudi Arabia was 55.7 ± 3.6%. Many socio-demographic variables were significantly associated with mean scores of knowledge of HIV/AIDS transmission modes, mean scores of attitude toward HIV/AIDS infected people, and mean scores of attitude toward the level of HIV/AIDS awareness (P-value ≤ 0.05). The Spearman rank correlation explained significant negative linear correlations between knowledge of HIV/AIDS transmission modes-attitudes toward HIV/AIDS infected people and knowledge of HIV/AIDS transmission modes-attitudes toward the level of HIV/AIDS awareness of r = −0.040 and r = −0.070, respectively (P-value ≤ 0.05). Otherwise, there was a positive linear correlation between attitudes toward HIV/AIDS infected people-attitudes toward the level of HIV/AIDS awareness (r = 0.080, P-value = 0.072).ConclusionsThe study showed that a high percentage of the respondents had good knowledge of HIV/AIDS transmission modes. However, a low rate of the study respondents had positive attitudes toward HIV/AIDS infected people and the level of HIV/AIDS awareness among the general population in Saudi Arabia. Therefore, there is a dire need for advocacy campaigns and policies to help reduce HIV stigmatization levels.